Implementasi Keterampilan Mengadakan Variasi pada Pembelajaran PAI di Sekolah SMPN 6 Sangatta Utara - Sa’baniah, Sa’baniah; Srinanda, Srinanda; Ningsih, Iin Suriya; Faelasup, Faelasup (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
Learning Implementation is a way of processing information through actions that occur between teachers and students either directly or indirectly. A teacher must have some basic teaching skills to run an efficient, entertaining, and more capable class and ensure that learning occurs at the highest level possible. Possible. Among the basic teaching skills that are important for a teacher to have, one of them is the skill in carrying out variations, where variation itself is a change in the activity process which aims to increase students’ learning motivation, in order to reduce boredom and boredom. With the hope that the variety of learning processes provided will bring positive things to light for students in the field, providing variations in PAI learning at SMPN 6 Sangatta Utara shows that students can master the material in PAI subjects so that the results achieved can be maximized. For this reason, this research examines the implementation of skills in providing variations in Islamic Religious Education learning at SMPN 6 Sangatta Utara. The data collection method in this research was interviews, observation and documentation. Then the data was analyzed using the Miles and Huberman Model interactive analysis technique with data reduction, data presentation and data verification steps, and its validity was tested using the time triangulation technique. The results of the research show that the implementation of skills in providing variations in Islamic Religious Education subjects at SMPN 6 Sangatta Utara has been implemented well by Islamic religious education teachers during the learning process. Learning variations are carried out by teachers by holding various variations, such as: variations in teaching styles, variations in the use of teaching media, and variations in interaction patterns